Dyspnea, Massive Effusion and Lytic Rib Lesion as Initial Presentation of Multiple Myeloma in a Young Man - Mohammed H AlShati; Ramesh Kumar; Shreeram Kannan (Canadian Respiratory Journal)
Multiple myeloma, a disorder commonly encountered in elderly patients, represents a malignant proliferation of plasma cells that primarily affects bone marrow. Pleural effusion as the presenting manifestation of the disease is uncommon. The authors report a case of multiple myeloma with unusual features presenting at a relatively young age with massive spontaneous hemothorax and multiple thoracic masses completely obscuring rib shadow on plain chest imaging. The patient demonstrated a good response to melphalan chemotherapy without recurrence of effusion or the need for additional chemical or surgical pleural interventions.